Pengaruh Pembesaran Dimensi Pile Terhadap Kekuatan Struktur Pile Slab - Eko Walujodjati Walujodjati; Zulfikar Cholik (Siklus : Jurnal Teknik Sipil, 2022)
The Kapalbetung Toll Road or KAPB (Kayu Agung-Palembang-Betung) has a Pile Slab design on soft ground. Handling by improving the embankment soil, using a vacuum or stone column method is unsuitable for existing soil conditions that are waterlogged throughout the year. Initial Spun Pile D-60 cm resulted in displacement/deflection and moment capacity that did not meet the requirements. Structural reinforcement was needed to overcome the excessive displacement and minimize the Ultimate Moment on the piles. Alternatives for handling structures such as backfilling, concrete bracing, or steel bracing are considered to have extraordinary consequences. This study aims to find other alternatives in overcoming these problems. Through structural analysis by increasing the dimensions of the Spun Pile (piles) which are engineered to meet the provisions contained in the toll road planning. Enlargement of the cross-section of the piles from spun pile D-60 cm to spun pile D-120 cm, produces displacement and moment values ​​that meet the requirements. With an increase in the dimensions of the diameter of the spun pile by 100%, the displacement decreases by 72% and when the moment meets the requirements for the maximum limit of the moment capacity of the spun pile according to the manufacturer's brochure